Business Process Management 9th International Conference, BPM 2011, Clermont-Ferrand, France, August 30 - September 2, 2011. Proceedings - Rinderle-Ma, Stefanie; Toumani, Farouk; Wolf, Karsten; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Business Process Management, BPM 2011, held in Clermont-Ferrand, France, in August/September 2011. The volume contains 22 revised full research papers carefully reviewed and selected from 157 submissions, as well as 5 industrial track papers and abstracts of three invited talkes. The papers address innovative research of highest quality from computer science, management information science, service-oriented computing, and technology management.
Keywords: Computer science; Software engineering; Logic design; Information systems; Management information systems; Computer Science; Information Systems Applications (incl.Internet).; User Interfaces and Human Computer Interaction; Software Engineering; Logics and Meanings of Programs; Computer Appl. in Administrative Data Processing; Business Information Systems